Case Report: Acral vasculitis induced by Immune Checkpoint Inhibitors: a case series and literature review - Rivet, Valérian; Guillon, Benoit; Sibaud, Vincent; Dion, Jérémie; Pastissier, Andréa; Delavigne, Karen; Cougoul, Pierre; Rauzy, Odile; Comont, Thibault (Frontiers in Oncology, 2025)
IntroductionImmune Checkpoint Inhibitors (ICIs) may cause various immune- related Adverse Events (irAEs). Of these events, vascular involvement is still considered an uncommon irAEs and generally concerns large or medium vessels. Acral small-vessel vasculitis can lead to severe digital necrosis.Case presentationHerein, we present three cases after treatment with pembrolizumab, nivolumab, and combination nivolumab/ipilimumab for lung adenocarcinoma, renal cell carcinoma, and melanoma, respectively. Two patients had a Raynaud’s-like syndrome. All of them presented with digital ischemia of both hands and with severe acral necrosis in the first case. Management consisted in ICI discontinuation, high-dose steroids, and vasodilator agents with good evolution in the three cases. No rechallenge of ICI has been attempted.DiscussionWe found 12 other cases in the literature review to build a cohort of 15 patients, mostly male with a median age of 60 years. Lung cancer and melanoma are the most common tumors. The most frequently used ICI was pembrolizumab. The median time to onset was 8 weeks. The main clinical presentation was a distal and painful necrosis mostly on thehands with bilateral involvement. Toes were affected in only two cases. All cases were severe features with grade ≥ 3. Eleven patients were treated with steroids and vasodilator agents. ICI was discontinued permanently in all patients.ConclusionICI-induced small-vessel vasculitis can lead to severe digital ischemia, often in males, and is preceded by a Raynaud’s-like syndrome with mostly bilateral and hand involvement. Data are still missing to optimize management of these kinds of patients.